COVID-19 in Nepal: Impacts on Production, Poverty & Food Systems - Pradesha, Angga; Thapa-Parajuli, Resham; Diao, Xinshen (2021)
Prepared by Angga Pradesha1, Resham Thapa-Parajuli2 & Xinshen Diao1 1. International Food Policy Research Institute 2. Tribhuvan University, Nepal Last updated: 3 May 2021